The Unfolded Protein Response Protects from Tau Neurotoxicity In Vivo - Loewen, Carin A. (Public Library of Science, 2010)
The unfolded protein response is a critical system by which the cell handles excess misfolded protein in the secretory pathway. The role of the system in modulating the effects of aggregation prone cytosolic proteins has received less attention. We use genetic reporters to demonstrate activation of the unfolded protein response in a transgenic Drosophila model of Alzheimer's disease and related tauopathies. We then use loss of function genetic reagents to support a role for the unfolded protein response in protecting from tau neurotoxicity. Our findings suggest that the unfolded protein response can ameliorate the toxicity of tau in vivo.